Environmental enrichment in middle age rats improves spatial and object memory discrimination deficits - Magdalena Miranda; Maria Carla Navas; Maria Belen Zanoni Saad; Dinka Piromalli Girado; Noelia Weisstaub; Pedro Bekinschtein (Frontiers in Behavioral Neuroscience)
Changes in memory performance are one of the main symptoms of normal aging. The storage of similar experiences as different memories (ie. behavioral pattern separation), becomes less efficient as aging progresses. Studies have focused on hippocampus dependent spatial memories and their role in the aging related deficits in behavioral pattern separation (BPS) by targeting high similarity interference conditions. However, parahippocampal cortices such as the perirhinal cortex are also particularly vulnerable to aging. Middle age is thought to be the stage where mild mnemonic deficits begin to emerge. Therefore, a better understanding of the timing of the spatial and object domain memory impairment could shed light over how plasticity changes in the parahipocampal-hippocampal system affects mnemonic function in early aging. In the present work, we compared the performance of young and middle-aged rats in both spatial (spontaneous location recognition) and non-spatial (spontaneous object recognition) behavioral pattern separation tasks to understand the comparative progression of these deficits from early stages of aging. Moreover, we explored the impact of environmental enrichment (EE) as an intervention with important translational value. Although a bulk of studies have examined the contribution of EE for preventing age related memory decline in diverse cognitive domains, there is limited knowledge of how this intervention could specifically impact on BPS function in middle-aged animals. Here we evaluate the effects of EE as modulator of BPS, and its ability to revert the deficits caused by normal aging at early stages. We reveal a domain-dependent impairment in behavioral pattern separation in middle-aged rats, with spatial memories affected independently of the similarity of the experiences and object memories only affected when the stimuli are similar, an effect that could be linked to the higher interference seen in this group. Moreover, we found that EE significantly enhanced behavioral performance in middle-aged rats in the spatial and object domain, and this improvement is specific of the high similarity load condition. In conclusion, these results suggest that memory is differentially affected by aging in the object and spatial domains, but that BPS function is responsive to an EE intervention in a multidomain manner.